CODE OF CONDUCT OF GOOD CORPORATE GOVERNANCE AT SHARIA BANK - kartika Sharaswati; W Wulandari; Husnul Khotimah Sylvia; Heru Kuswandito (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2020)
As the development of Islamic Banks the importance of ethical values ​​and norms can strengthen the bank's reputation for customers. Therefore, it is necessary to have a deep understanding for every banking person towards the Code of Conduct guidelines that better adjusts to business developments and applicable regulations and realizes the best practices of sharia banking that can prevent the occurrence of forms of irregularities (fraud) that might occur at Islamic banks. The implementation of Good Corporate Government is one tool to build the trust of customers, the community and the international community which is an absolute requirement for a bank institution to develop. Therefore, it is necessary to apply Good Corporate Government in Islamic banks that adjust to Islamic principles in banking operations. The role of the Sharia Supervisory Board (DPS) in Good Corporate Government in Islamic banks is very important to supervise and guarantee that the bank's operations are in accordance with Islamic principles. In other words, the implementation of Good Corporate Government will affect the banking code of ethics which is an important factor in carrying out day-to-day operations of the bank.